(untitled) (Progress Annals: Journal of Progressive Research, 2024)
In this article, young engineers studying at a technical university are brief thoughts and comments on self-help developed on the basis of competence production, the use of methods and technology based on specific characteristics to obtain a judicial professional appearance. done . It is no exaggeration to say that the organization of the educational process in a methodical, non-traditional way, using information and communication technologies, is the main ground for the growing young generation to become mature specialists.